A century of India’s economic transformation: a critical review - Kalim Siddiqui (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2019)
The objective of this study is to examine India’s transformation from a colonial to a modern economy on the basis of the macro-economic level changes that have occurred over the last century. This is important because it will help us to understand the associated growth performance and its impact on sectoral changes and employment in the wider context of developing economies such as India. The methodology to be followed here is derived from the aims of the study and comparisons of international statistics that provide the means by which to address the research questions and the objectives of this paper. The study found that during the colonial period, the Indian economy became subservient rather than sovereign in terms of policy matters. As a result, economic development was hampered by the removal of ‘surplus’, along with very high land rents and tribute charges. A densely populated country like India was drawn into the orbit of exploitation in the mid-18th century. Soon after independence in 1947, the Indian government took a number of initiatives to enhance industrial and agricultural development, but the biggest failure was that it did not make any real impression on the country’s huge unemployment problems.